2021
DOI: 10.3389/fonc.2021.642940
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Multifunctional Protein p32 Promotes a Malignant Phenotype in Colorectal Cancer Cells

Abstract: p32 is a multifunctional and multicompartmental protein that has been found upregulated in numerous adenocarcinomas, including colorectal malignancy. High levels of p32 expression have been correlated with poor prognosis in colorectal cancer. However, the functions performed by p32 in colorectal cancer have not been characterized. Here we show that p32 is overexpressed in colorectal cancer cell lines compared to non-malignant colon cells. Colon cancer cells also display higher nuclear levels of p32 than nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…C1QBP interacts with gC1q of C1q, and is involved in the regulation of T cell immunity and regulation of cytokines ( Ricklin et al, 2010 ). C1QBP was found to be closely related to tumorigenesis or metastasis of various cancers ( Bai et al, 2019 ; Xie et al, 2019 ; Peerschke et al, 2020 ; Egusquiza-Alvarez et al, 2021 ; Xie et al, 2021 ). C1S was also observed to promote tumor growth and survival in renal cancer and cutaneous squamous cell carcinoma ( Riihila et al, 2020 ; Daugan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…C1QBP interacts with gC1q of C1q, and is involved in the regulation of T cell immunity and regulation of cytokines ( Ricklin et al, 2010 ). C1QBP was found to be closely related to tumorigenesis or metastasis of various cancers ( Bai et al, 2019 ; Xie et al, 2019 ; Peerschke et al, 2020 ; Egusquiza-Alvarez et al, 2021 ; Xie et al, 2021 ). C1S was also observed to promote tumor growth and survival in renal cancer and cutaneous squamous cell carcinoma ( Riihila et al, 2020 ; Daugan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HIF-1α has been associated with growth, metastasis and treatment resistance in breast cancer by activating the PI3K/Akt/mTOR pathway [ 44 ]. C1QBP has also been implicated in Akt/mTOR signaling, which affects the migration capability of colon cancer cells [ 45 ]. TNBCs are reported to have increased expression of HIF-1α [ 46 ] and recently, Wu et al showed that HIF-1α upregulates C1QBP in TNBCs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have shown that gC1qR contributes to cancer progression, invasion and metastasis, and correlates with clinicopathological features of tumors ( Figure 1 ) ( 23 , 52 55 ). Its overexpression was found in multiple cancer cells, including breast, ovarian, prostate, melanoma, lung, pancreatic, colon cancer, and malignant pleural mesothelioma ( 55 58 ). It has been reported the expression level of gC1qR was correlated with tumor stage, grade, tumor size, and clinical outcome ( 59 , 60 ).…”
Section: Gc1qr In Cancermentioning
confidence: 97%